Pengolahan Limbah Cair Laundry Menggunakan Membran Ultrafiltrasi Aliran Cross Flow dengan Variasi Tekanan Transmembran dan Konsentrasi Chemical Cleaning Agent (NaOH) - Eqiu Alkahfi Tarif (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
Ultrafiltration membrane is one of wastewater treatment technologies, but membranes have limitations such as the occurrence of the phenomenon of concentration polarization and fouling. The research objective of this study the effect of variations in transmembrane pressure against the rejection percentage COD, TSS, and the effect of variations in transmembrane pressure, concentration of washing of the efficiency and effectiveness of washing the membrane. The process of ultrafiltration membranes and membrane chemical washing wastewater laundry do with variations in pressure of 1 bar, 2 bar, and 3 bar. Variation of chemical cleaning agent concentration of 1%, 1.5% and 2%, rinsing with distilled water for 30 minutes, filtering wastewater laundry for 120 minutes, and washing using chemical cleaning agent (NaOH) for 30 minutes. Highest rejection percentage for COD parameter 86.6% and 85.7% for TSS parameters in transmembrane pressure of 3 bar. The highest washing efficiency of the value of Flux Recovery (FR) gained 81.9%, and the value of resistance of Removal (RR) gained 82.59% with a concentration of 2% in the transmembrane pressure of 3 bar. The highest leaching effectiveness obtained at 50.21% with a concentration of 2% and a transmembrane pressure of 3 bar.